(untitled) (Research, Society and Development, 2021)
Objective: to assess, based on a systematic review, what the crack and fracture rate in ceramic veneer is, in order to establish the main causes for these failures. Methodology: A systematic review of prospective and retrospective clinical studies that analyzed the failure rate due to cracks or fractures in the restoration of teeth restored with ceramic veneers was carried out. The descriptors “ceramic” and “veneer” were used, adapted according to the databases consulted: Science Direct, LILACS, MEDLINE (PubMed) and Google Scholar. Initially, 755 articles were found, after reading and applying the eligibility and exclusion criteria, 4 articles were selected for the quantitative and 5 for the qualitative analyses. This review followed the recommendations of the Preferred Reporting Items for Systematic Reviews and Meta-analyzes (PRISMA). Results: Marginal discoloration was the most commonly found failure (17.2%), followed by periodontal or gingival inflammation (12.8%), debonding (4.4%), crack of ceramic (2.7%) and fracture of ceramic (1.7%). Failures due to endodontic injury, secondary caries, tooth fracture and color change of the ceramic were less than 1%. Conclusion: Attention to occlusion, its studies and concepts, must be taken into account in the entire process of treatment with ceramic veneers to ensure longevity and clinical success.